Proteinase Activity in Jawala Prawns (Acetes Indicus) at Alkaline pH - S.V., Sherekar; Chander, Ramesh; M.N., Karani; S.B., Warrier; M.S., Gore; Thomas, Paul (Fishery Technology, 2012)
Proteolytic activity of Jawala (Acetes indicus), a tiny crustacean, was examined. Caseinolytic activity of Jawala was many times more than that of the muscle of fish and prawn species. The high proteolytic activity of Jawala was principally located in the head region which contains hepatopancreas. Caseinolytic activity was inhibited partially by many inhibitors. Protoelytic activity when partially purified had a pH optima of 8.5 with azocasein and optimum activity between 50 - 550C. It was also stable for one hour at 50oC, but loss of activity occured at higher temperatures.